Community rehabilitation in neurology - Barnes, Michael P., 1952- (Cambridge University Press, 2003)
Analyses community rehabilitation needs from many different perspectives. Many examples of community rehabilitation schemes are presented, and case studies are used to highlight the main issues. The authors take an international view, and there are chapters dealing with the disabled child in the community and with neuropsychological rehabilitation.
Keywords: Nervous system -- Diseases -- Patients -- Rehabilitation.; Community health services.; Nervous System Diseases -- rehabilitation; Community Health Services; Système nerveux -- Maladies -- Patients -- Réadaptation.; Services communautaires de santé.; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology.; Community health services; Nervous system -- Diseases -- Patients -- Rehabilitation